Analisa Keandalan Sistem Distribusi Penyulang Kampus dengan Menggunakan Penggabungan Metode Section Technique dan Ria - Arigandi, Gusti Putu Budi; Hartati, Rukmi Sari; Weking, Antonius Ibi (Majalah Ilmiah Teknologi Elektro, 2015)
There was many reliability system research with several research method. Each method have their adventages and disadventages, such as Section Technique method and RIA method. Section Technique method have adventage in its easy calculation, while RIA method use momentary failure rate parameter in its calculation so its final result almost similar to research place. Based on calculation result with Section Technique method found that SAIFI value of Kampus feeder network is 0,085 times / customer / years and SAIDI value of Kampus feeder network is 0,107 minutes / customer / years. After add momentary failure rate parameter to the calculatio, found that SAIFI value of Kampus feeder network is increase to 0,094 times / customer / years and SAIDI value of Kampus feeder network is increase to 0,162 minutes / customer / years.
Keywords: Section Technique, RIA, Indeks Keandalan